The princess diarist - Fisher, Carrie (Blue Rider Press, 2016)
"When Carrie Fisher recently discovered the journals she had kept during the filming of the first Star Wars movie, she was astonished to see what they had preserved--plaintive love poems, unbridled musings with youthful naiveté, and a vulnerability that she barely recognized. Today her fame as an author, actress, and pop-culture icon is indisputable, but in 1976, Carrie Fisher was just a teenager with an all-consuming crush on her costar. With these excerpts from her handwritten notebooks, The Princess Diarist is Fisher's intimate and revealing recollection of what happened on one of the most famous film sets of all time--and what developed behind the scenes ... Fisher also ponders the joys and insanity of celebrity as well as the absurdity of a life spawned by Hollywood royalty whose lofty status has ultimately been surpassed by her own outer-space royalty"--Jacket.